Efficacy and reinfection with soil-transmitted helminths 18-weeks post-treatment with albendazole-ivermectin, albendazole-mebendazole, albendazole-oxantel pamoate and mebendazole. Issue 1 (December 2016) - Speich, Benjamin; Moser, Wendelin; Ali, Said; Ame, Shaali; Albonico, Marco; Hattendorf, Jan; Keiser, Jennifer
Abstract Background Preventive chemotherapy with albendazole or mebendazole is the current strategy to control soil-transmitted helminth (STH) infections (i.e.Ascaris lumbricoides, hookworm andTrichuris trichiura ). STH reinfections, in particularA. lumbricoides andT. trichiura occur rapidly after treatment with the standard drugs. However, their low efficacy againstT. trichiura, made an accurate assessment of reinfection patterns impossible. Methods In 2013 a randomised controlled trial was conducted on Pemba Island, Tanzania. School-aged children diagnosed positive forT. trichiura, were randomly allocated to (i) albendazole-ivermectin; (ii) albendazole-mebendazole; (iii) albendazole-oxantel pamoate; or (iv) mebendazole. Here we report the efficacy [cure rates (CR) and egg-reduction rates (ERR)], reinfection rates and new infections determined 18 weeks post-treatment. Results For a total of 405 children complete baseline and follow-up data were available. Similar to the efficacy determined after 3 weeks, 18 weeks after treatment albendazole-oxantel pamoate showed a significantly higher efficacy againstT. trichiura (CR: 54.0 %, 95 % CI: 43.7–64.0; ERR: 98.6 %, 95 % CI: 97.8–99.2) compared to the other treatment arms. Children treated with albendazole-oxantel pamoate or albendazole-ivermectin had fewer moderate infections compared to children treated with albendazole. The reinfection rates 18 weeks post-treatment among all treatment arms were 37.2 % forT. trichiura (95 % CI: 28.3–46.8), 34.6 % forA. lumbricoides (95 % CI: 27.3–42.3) and 25.0 % for hookworms (95 % CI: 15.5–36.6). Conclusion The moderate reinfection rates with STHs 18 weeks post-treatment support the concept of regular anthelminthic treatment in highly endemic settings. Combination chemotherapy might achieve decreased morbidity in children since in the albendazole plus oxantel pamoate and albendazole plus ivermectin treatment arms only few moderateT. trichiura infections remained. Further trials should investigate the long term efficacy of albendazole-oxantel pamoate (i.e. 6 and 12 month post-treatment) and after several rounds of treatment in order to develop recommendations for appropriate control approaches for STH infections. Trial registration Current Controlled TrialsISRCTN80245406